LEGAL CERTAINTY ARTICLE 15 PARAGRAPH (3) LAW NUMBER 2 OF 2014 CONCERNING AMENDMENT TO LAW NUMBER 30 OF 2004 CONCERNING NOTARIES - Rubby Aditya Panglima; Benny Djaja (UNES Law Review, 2023)
This study discusses the ambiguity of norms in Article 15 paragraph (3) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notaries (Amendments to the Notary Law) which affect legal certainty in the regulation of the authority of a notary related to "authority others regulated in the Legislation". This provision causes confusion regarding the scope and limits of a notary's authority in carrying out his duties. This study also analyzes the impact of the ambiguity of these norms on the implementation of the authority of a notary in legalizing electronic transactions. Through a normative legal research approach, the author analyzes the relevant articles in the Notary Law and related laws and regulations to understand the legal context related to the authority of a notary. This research finds that the ambiguity of norms in Article 15 paragraph (3) creates ambiguity regarding the limits and scope of a notary's authority in terms of "other authorities regulated in Laws and Regulations". The impact of the ambiguity of this norm can be seen in the implementation of the authority of a notary in legalizing electronic transactions. Without clarity regarding the scope of this authority, notaries may face difficulties in determining whether they have the authority to certify certain electronic transactions, which in turn can affect the legal certainty in such transactions. This study suggests the need for clarification of norms in Article 15 paragraph (3) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notaries. A clear clarification will provide clarity to notaries regarding the limits and scope of their authority in relation to "other authorities stipulated in Laws and Regulations", so as to increase legal certainty and the effectiveness of the implementation of notary powers in validating electronic transactions.